1974
DOI: 10.1073/pnas.71.8.2946
|View full text |Cite
|
Sign up to set email alerts
|

Met-tRNA f Met Binding to 40S Ribosomal Subunits: A Site for the Regulation of Initiation of Protein Synthesis by Hemin

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 34 publications
4
72
0
Order By: Relevance
“…The capacity of the A chain to inhibit ribosomai protein synthesis after conjugation to the antibody was assayed in a rabbit reticulocyte cell-free system [7] and found to be unimpaired. Binding of the conjugate was assessed by the measurement of iz51-labelled sheep anti-rat y 2 on the target cells.…”
Section: B Chain Fibrosarcomamentioning
confidence: 99%
“…The capacity of the A chain to inhibit ribosomai protein synthesis after conjugation to the antibody was assayed in a rabbit reticulocyte cell-free system [7] and found to be unimpaired. Binding of the conjugate was assessed by the measurement of iz51-labelled sheep anti-rat y 2 on the target cells.…”
Section: B Chain Fibrosarcomamentioning
confidence: 99%
“…The haemin-regulated inhibitor, double-stranded RNA, oxidized glutathione and the inhibitor found in lysates prepared from leukaemic cells all inhibit initiation of protein synthesis (Legon et al, 1974;Cimadevilla & Hardesty, 1975) and thus are different from the inhibitor found in muscle. Moreover the haemin-regulated inhibitor has no effect on poly(U)-directed protein synthesis (Clemens et al, 1974). Furthermore, the addition of haemin to our incubation assay does not remove the inhibitory activity.…”
Section: Discussionmentioning
confidence: 78%
“…The polypeptide-chain-initiation factor eIF-2 has been implicated in several examples of translational control of protein synthesis in animal cells (Clemens et al, 1974;Lebleu et al, 1976;Farrell et al, 1977;Kay et al, 1979;Pain et al, 1980; see also review by Austin & Clemens, 1980). We have shown that starvation of Ehrlich ascites-tumour cells for a single essential amino acid results in inhibition of initiationcomplex formation on native 40S ribosomal subunits both in intact cells (Pain & Henshaw, 1975) and in extracts prepared from them .…”
mentioning
confidence: 91%